An Empirical Assessment of Success Factors Boosting Zimbabwean Banking Consumer Confidence - Andrew Mwatetsera; Maxwell Sandada; Tinashe Chuchu; Eugine Tafadzwa Maziriri (Journal of Economics, Business, and Accountancy Ventura, 2021)
Consumer confidence is a crucial factor determining a bank's performance. This study examines the key success factors for increasing bank customer confidence in Zimbabwe. Three research objectives were set and explored using a quantitative survey approach with a sample of 426 bank employees and customers to establish the critical success factors for restoring consumer confidence in Zimbabwe. The critical success factors to restore consumer confidence in the banking sector in Zimbabwe are found in this current study using Exploratory Factor Analysis (EFA). The results indicated that the essential factors of success to be implemented to restore consumer confidence in banks in Zimbabwe are customer satisfaction, location and convenience, product range or size of the bank, digitalization of the processes, service culture, bank relationships, and market position of the bank. The study recommended that the banking and financial services sectors in Zimbabwe should offer more customer satisfaction-driven products, improve the product range, be available in different locations and offer convenient services to the customers. These should be coupled with prompt handling of customers' complaints through different channels and digitalization of the banking processes to enhance banking relationships and restore consumer confidence.